If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying a = (3a + -7) Reorder the terms: a = (-7 + 3a) Remove parenthesis around (-7 + 3a) a = -7 + 3a Solving a = -7 + 3a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-3a' to each side of the equation. a + -3a = -7 + 3a + -3a Combine like terms: a + -3a = -2a -2a = -7 + 3a + -3a Combine like terms: 3a + -3a = 0 -2a = -7 + 0 -2a = -7 Divide each side by '-2'. a = 3.5 Simplifying a = 3.5
| 6(x+16)= | | (5x+2)(5x+2)=144 | | X-8=-4-26 | | 7x-3x-50=20 | | y-2(y-3)+4= | | 2x+3x-5=50 | | 35z-11=59 | | x=6(2x+1) | | -4-6=5x+9-4x | | 0(8b+4)= | | 26R-3R^2=0 | | 11x+3=2x | | -75=-3x+3 | | 4x-9-9-8x= | | 5j-j= | | X+X+10+2(2X+10)=180 | | 8h-4h= | | -9t+3=-10t | | 2x-(4y-3)+5+-3+-1= | | -(4xy-10)+3(3xy+6)= | | 6+4r=5r | | 3-3*6-2=12 | | 18-r=-323 | | -15x-14= | | 4x-1=10x+8 | | 22+z=-180 | | Y=x+-5 | | 249=4x^2+32x-11 | | 8-d=d-6 | | 7+5j=6j | | Ax-y+z=6 | | -0.03x+0.11(x+16000)=2080 |